Pengaruh Kotoran Bebek Terhadap Pertumbuhan Dan Hasil Tanaman Selada Pada Tanah Ultisol - ana, rupiana (Jurnal Sains Pertanian Equator, 2014)
ABSTRACT DUCK DIRT EFFECT ON THE GROWTH AND RESULTS TO LETTUCE PLANTS ON ULTISOL SOIL Rupiana(1), Siti Hadijah2), Setia Budi(2) (1) Student Of Agriculture Faculty(2) The Lecturer Of Agriculture Faculty Of Tanjungpura University Pontianak The utilization of ultisol soil lettuce plants was limited in some factors which are poor physical, ehemical, and biological condition. Giving duck manure on ultisol soil is one way to solve this problem. This study was done to determine the effect and optimal dose of duck manure to growth and yield of lettuce plants in ultisol soil. The experiment was conducted the experimental farm of Agriculture faculty, Tanjungpura Universitas. The study from date twenty two October arrive twenty tree year November two thousand and thirteen. The method used in this research is completely randomized desigs (CRD) which consist of 6 treatment level, repeated 4 times and each treatment contained 3 plant samples the provision of duck dirt treatments given here are: (b0:0g/polybag), (b1:300g/polybag), (b2:600g/polybag), (b3:900g/polybag), (b4:1200g/polybag), (b5:1500g/polybag), the variables observation was undertaken here consist of: number of leaver, leaf area, fresh weight, dry weight, root volume, leaf greenness. Revel temperature, humidity and soil ph was also taken in addition to the observation variables. Result of the variance analysis shows that the number leaves on the second to the fourth week and the root volume didn’t give significant effect while significant effect showed on leaf area, fresh weight, dry weight, leaf greenness level. The best dose of duck dirt is on b5 treatment, which is 1500/polybag. Keywors : duck dirt, ultisol, lettuce,